The G Protein‐Coupled Receptor 55 Ligand l‐α‐Lysophosphatidylinositol Exerts Microglia‐Dependent Neuroprotection After Excitotoxic Lesion. Issue 11 (3rd September 2013) - Kallendrusch, Sonja; Kremzow, Stine; Nowicki, Marcin; Grabiec, Urszula; Winkelmann, Ria; Benz, Alexander; Kraft, Robert; Bechmann, Ingo; Dehghani, Faramarz; Koch, Marco
<x xml:space="preserve">Abstract</x> Searching for chemical agents and molecular targets protecting against secondary neuronal damage reflects one major issue in neuroscience. Cannabinoids limit neurodegeneration by activation of neuronal G protein‐coupled cannabinoid receptor 1 (CB1) and microglial G protein‐coupled cannabinoid receptor 2 (CB2). However, pharmacological experiments with CB1/CB2‐deficient mice unraveled the existence of further, so‐called non‐CB1/non‐CB2 G protein‐coupled receptor (GPR) subtypes. GPR55, whose function in the brain is still poorly understood, represents a novel target for various cannabinoids. Here, we investigated whether GPR55 reflects a potential beneficial target in neurodegeneration by using the excitotoxicity in vitro model of rat organotypic hippocampal slice cultures (OHSC). l‐α‐Lysophosphatidylinositol (LPI), so far representing the most selective agonist for GPR55, protected dentate gyrus granule cells and reduced the number of activated microglia after NMDA (50 µM) induced lesions. The relevance of GPR55 activation for LPI‐mediated neuroprotection was determined by using Gpr55 siRNA. Microglia seems to mediate the observed neuroprotection since their depletion in OHSC attenuated the beneficial effects of LPI. Moreover, LPI alone induced microglia chemotaxis but conversely significantly attenuated ATP triggered microglia migration. These effects seemed to be independent from intracellular Ca2+ and p38 or p44/p42 MAPK phosphorylation. In conclusion, this study unmasked a yet unknown role for GPR55 in neuroprotection driven by LPI‐mediated modulation of microglia function. GLIA 2013;61:1822–1831